Correlation between vanadium carbide size and hydrogen trapping in ferritic steel. (15th July 2018) - Turk, Andrej; San Martín, David; Rivera-Díaz-del-Castillo, Pedro E.J.; Galindo-Nava, Enrique I.
Abstract: Hydrogen trapping on vanadium carbides (VC) was studied in a low-carbon ferritic steel. Thermal desorption analysis was performed on two conditions with different carbide sizes but identical volume fractions. Smaller carbides with a higher effective surface area trapped significantly more hydrogen. A correlation between carbide size and hydrogen trap density was established, suggesting that trapping is surface-dominant and a scaling law for trap density was derived. The amount of trapped hydrogen was overall much lower than previously reported for VC-containing martensitic steels. It is therefore suggested that in the absence of a dislocated matrix VC traps relatively little hydrogen. Graphical Abstract: